An Analysis Of Employment Termination For Freelance Workers: A Justice Approach From Islamic Economic Law - Faizin, Mu'adil; Zahra, Dhea Thalesya; Lutfina, Lutfina; Riyandani, Seja (Universitas Islam Negeri Raden Intan Lampung, 2024)
Freelance work is increasingly popular in today's digital economy due to its flexibility and opportunities to work with various clients. However, freelance workers often face legal uncertainties, especially concerning termination of employment. This phenomenon is significant in Indonesia as freelancers do not always receive adequate legal protection compared to regular employees. This study examines the legal consequences of employment termination for freelance workers from the perspective of Islamic economic law. The research formulates issues related to the lack of legal protection, which leads to uncertainty for freelance workers in employment termination, and seeks solutions to enhance legal certainty and their protection. The research method used is the theoretical analysis based on studying labour law, Islamic economic law, and regulations related to freelancers in Indonesia. The findings indicate that freelance workers must have clear legal protection for service agreements, fair income rights, and adequate social security. Implementing principles of justice and balance from Islamic economic law is expected to improve these conditions. Thus, the study recommends developing more inclusive regulations to enhance legal certainty and welfare for freelance workers in Indonesia. The conclusion emphasizes the need for better legal protection for freelance workers, taking into account the principles of Islamic economic law, to provide better protection for their rights, reduce uncertainty, and enhance fairness in freelance employment relationships in Indonesia.Keywords: Freelance Workers; Islamic Economic Law; Legal Protection; Termination of Employment